2013
DOI: 10.5847/wjem.j.issn.1920-8642.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

General characteristics of patients with electrolyte imbalance admitted to emergency department

Abstract: BACKGROUND:Fluid and electrolyte balance is a key concept to understand for maintaining homeostasis, and for a successful treatment of many metabolic disorders. There are various regulating mechanisms for the equilibrium of electrolytes in organisms. Disorders of these mechanisms result in electrolyte imbalances that may be life-threatening clinical conditions. In this study we defined the electrolyte imbalance characteristics of patients admitted to our emergency department.METHODS:This study was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 15 publications
3
46
1
9
Order By: Relevance
“…Balci et al also observed in their study that the patients who had hyperkalemia, the most frequent diagnosis were sepsis, infections and renal failure. (1) In our study, we also observed the higher blood urea levels in 32.08% patients and raised creatinine levels in 20.53% patients. This can be attributed to lack of proper fluid treatment, use of medicines which are nephrotoxic and infections were the main factors related with acute kidney failure.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Balci et al also observed in their study that the patients who had hyperkalemia, the most frequent diagnosis were sepsis, infections and renal failure. (1) In our study, we also observed the higher blood urea levels in 32.08% patients and raised creatinine levels in 20.53% patients. This can be attributed to lack of proper fluid treatment, use of medicines which are nephrotoxic and infections were the main factors related with acute kidney failure.…”
Section: Discussionsupporting
confidence: 67%
“…Electrolyte disturbances are common in most of the diseases and in the management of various clinical disorders, the fluid and electrolyte balance must also be maintained. (1) While estimating the electrolytes, the imbalances in every electrolyte must be considered for effective treatment of the patient. The most common electrolyte imbalances are hypo-and hyper-states of sodium, potassium, chloride, calcium, and magnesium.…”
Section: Introductionmentioning
confidence: 99%
“…Studies about the clinical prevalence of electrolyte imbalances often report that these disorders are frequently seen in elderly and critically ill patients, and occur in the progression of diseases such as diabetes mellitus, acute or chronic renal failures, severe cardiovascular events like myocardial infarctions, etc. To summarize, disturbances in electrolyte balances are mathematically measurable biochemical parameters in the bloodstream that determines the clinical manifestations of interactions between metabolic events such as sepsis, hormones, vascular events, medications, hydration deficiencies, and renal physiology [6,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The main responsible organ for this regulation is the kidney, but other mechanisms like hormonal activities of antidiuretic hormone, aldosterone and parathyroid hormone are also involved in this process. The disorders of these systems may deteriorate the electrolyte balances and results in emergencies [6]. The present study was planned to study the Knowledge, Attitude and practice of general medical practitioners and specialty physicians regarding diseases of electrolyte imbalances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation